Integrated UAS platform with 5G technology and non-terrestrial networks: Orkney Islands scenario - Mohanta, Krishnakanth; Al-Rubaye, Saba; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The integration of fifth-generation (5G) technology with Non-Terrestrial Networks (NTN) holds transformative potential for Beyond Visual Line of Sight (BVLOS) operations of Uncrewed Aerial Systems (UAS) in rural regions. This paper presents a comprehensive architectural design that leverages satellite-enabled 5G networks to enhance connectivity in the Orkney Islands, Scotland, thereby improving the reliability and operational efficiency of UAS missions. By addressing the limitations of terrestrial networks, particularly in remote and underserved areas, the proposed flowchart ensures seamless data communication and transfer, facilitating real-time control and monitoring within the UAS platform. Simulations are conducted to validate the scenario for remote area connectivity. This work underscores the crucial role of NTN in advancing UAS operations, paving the way for innovative services and broader adoption of UAS technologies in rural settings.
Keywords: 40 Engineering; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Rural Health; Health Disparities; 7 Affordable and Clean Energy; SATCOM; Non-Terrestrial Networks; Network Architecture; UAS